Minimization of ragweed allergy immunotherapy costs through use of the sublingual immunotherapy tablet in Canadian children with allergic rhinoconjunctivitis - Anne K. Ellis; Douglas P. Mack; Rémi Gagnon; Eva Hammerby; Sheena Gosain (Allergy, Asthma & Clinical Immunology, 2023)
Abstract Background Allergy immunotherapy (AIT), in the form of subcutaneous immunotherapy (SCIT) with alum-precipitated aqueous extracts, SCIT with a modified ragweed pollen allergen tyrosine adsorbate (MRPATA; Pollinex®-R), or a sublingual immunotherapy (SLIT)-tablet are options for the treatment of ragweed pollen allergic rhinoconjunctivitis (ARC) in Canadian children. A cost minimization analysis evaluated the economic implications of the use of the ragweed SLIT-tablet vs SCIT in Canadian children with ragweed ARC. Methods A cost minimization analysis was conducted comparing the short ragweed SLIT-tablet, 12 Amb a 1-U, preseasonally with preseasonal ragweed SCIT, annual ragweed SCIT, or MRPATA. The analysis was conducted over a time horizon of 3 years from a public payer perspective in Ontario and Quebec. Resources and costs associated with medication and services of healthcare professionals were considered for each treatment. The resource and cost input values for the model were obtained from published literature and validated by Canadian clinical experts in active allergy practice. A discount rate of 1.5% was applied. Several scenario analyses were conducted to determine the impact of many of the key base case assumptions on the outcomes. Results Over the total 3-year time horizon, the ragweed SLIT-tablet had a potential cost savings of $900.14 in Ontario and $1023.14 in Quebec when compared with preseasonal ragweed SCIT, of $6613.22 in Ontario and $8750.64 in Quebec when compared with annual ragweed SCIT, and $79.62 in Ontario and $429.49 in Quebec when compared with MRPATA. The ragweed SLIT-tablet had higher drug costs compared with the other AIT options, but lower costs for healthcare professional services. The lower costs for healthcare professional services with the ragweed SLIT-tablet were driven by the need for fewer office visits than SCIT. Scenario analysis indicated that costs were most impacted by including societal costs (e.g., costs associated with patient/caregiver travel and time lost). The potential cost savings of the ragweed SLIT-tablet versus SCIT and MRPATA was maintained in most scenarios. Conclusions In this cost minimization analysis, the ragweed SLIT-tablet provided estimated cost savings from a public payer perspective for the treatment of ragweed ARC in Canadian children compared with SCIT or MRPATA.